Effect of cultivation factors on the yield and yield security of maize - Sárvári, Mihály (Acta Agraria Debreceniensis, 2012)
Cultivation factors have a significant effect on the yield and yield security of maize. Ensuring a suitable green crop is important. Tricultural crop rotation (pea–wheat–maize) in the average of 25 years provided a 2 t ha-1 higher yield compared to monocultural cultivation. A harmonious NPK nutriment supply determines yield and yield security, which can be especially realized by means of the application of precision cultivation technologies. Under average circumstances N 80 kg ha-1, P2O5 50 kg ha-1, K20 60 kg ha-1 active ingredient is the agro-ecological dosage of artificial fertilizer.Plant density is a factor that determines yield. Optimal plant density – beside the genetic characteristics of the hybrid – is mostly influenced by the level of water and nutriment supply.